Smart services : competitive information strategies, solutions, and success stories for service businesses - Sawyer, Deborah C., 1953- (Information Today, Inc., 2002)
Focusing specifically on the competitive information needs of service-oriented firms, this book illuminates the many forms of competition in service businesses, identifies the most effective information resources for competitive intelligence, and provides a practical framework for identifying and studying competitors in order to gain competitive advantage. Explained are unique challenges and techniques for tackling traditional competitors, uncovering hidden and left-field competition, discovering and tracking competitor strategies, looking for financial intelligence, and looking for intel.